Childhood Adversity and Mental Health Correlates of Obesity in a Population at Risk. (October 2016) - Brewer-Smyth, Kathleen; Cornelius, Monica; Pohlig, Ryan T.
The staggering prevalence of obesity and obesity-related health conditions takes exorbitant tolls on health care resources. This cross-sectional study with private evaluations of 636 adult inmates in a southern state prison was conducted with regressions comparing obese (body mass index [BMI] ≥ 30) to nonobese individuals to define obesity risk factors. Obese individuals more likely were female, were victims of childhood sexual abuse, suffered greater severity of childhood sexual abuse, attempted suicide, reported drug dependency, were non-Caucasian, and were older than nonobese. Psychopathy predicted lower BMI. Though obesity might be expected in victims of childhood physical abuse, traumatic brain injury, or other mental health conditions due to mobility or decision-making deficits, neither were significant. Adjusting for related variables, childhood sexual abuse remained significant. Females attempted suicide more frequently and suffered greater childhood sexual abuse.